2015
DOI: 10.1016/j.ijscr.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction secondary to greater omental encircling band–Unusual case report

Abstract: HighlightsSmall bowel obstruction (SBO) is a common occurrence in adult surgical procedures.About 60% of SBO are currently accounted for adhesion mainly due to previous laparotomy.Acute, non-postoperative SBO is less common.Preoperatively, it is often difficult to identify the cause of the ileus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Leading cause of small bowel obstruction is adhesions (60%), followed by hernia (25%) and neoplasm (5–10%) [2,3]. First adhesions were identified at post-mortem of a patient in 1836 [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leading cause of small bowel obstruction is adhesions (60%), followed by hernia (25%) and neoplasm (5–10%) [2,3]. First adhesions were identified at post-mortem of a patient in 1836 [4].…”
Section: Discussionmentioning
confidence: 99%
“…Acute small bowel obstruction, previously seen only with incarcerated hernia, is now attributed majorly to postoperative adhesions as an increasing number of abdominal surgeries are being performed for varying etiologies [1]. As much as 60–70% of intestinal obstructions are caused by adhesions [2,3]. Adhesions form in 63–97% of patients undergoing major abdominal surgery [3,4] Adhesive small bowel obstruction (ASBO) is a major cause of readmissions, accounting for 4.5% of readmissions in the first year following surgery [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On review of literature, SBO caused by omental banding is very rare with only few reported cases in the literature [ 4 7 ]. Sinwar reported a case of a 42-year-old male with SBO secondary to greater omental encasement without previous history of abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sinwar reported a case of a 42-year-old male with SBO secondary to greater omental encasement without previous history of abdominal surgery. Biopsy ultimately demonstrated tubercular granuloma on histological exam causing chronic inflammation [ 4 ]. The second case involved a 31-year-old male with SBO secondary to lesser omental encasement and only mild inflammation of the omentum on histological exam, also without any prior history of abdominal surgery [ 5 ].…”
Section: Discussionmentioning
confidence: 99%